Identificação de regiões com variação no número de cópias de segmentos de DNA em bovinos de raças autóctones espanholas - Silva, Thiago Bruno Ribeiro da [UNESP] (2015)
Copy number variation (CNV) are DNA segments that are present at variable copy number compared to a reference genome. Classes of CNVs include insertions, deletions, duplications and inversions. CNVs can be associated with gene expression and phenotypic variation, providing genetic variability among individuals and, thus, are an important tool to production and healthy traits selection. The goal of this study was to identify regions with copy number variation in a total of 366 individuals from 5 autochthonous Spanish breeds of beef cattle, distributed into 25 families for breed, composed of sire-dam-offspring, called trios. The animals belonged to Asturiana de los Valles (75 individuals, 25 trios), Avileña-Negra Ibérica (74 individuals, 24 complete trios, one sire-repeated trio), Morucha (Mo, 75 individuals, 25 trios), Pirenaica (74 individuals, 24 24 complete trios, one sire-repeated trio) e Retinta (68 individuals, 18 complete trios, 7 sire-repeated trios) and were genotyped with the Illumina BovineHD Beadchip. The PennCNV software performed the CNVs identification. The CNV regions (CNVR) were determined by the overlapping of the CNVs. Candidates genes placed within the found CNVRs were investigated by analysis into the NCBI and Ensembl data platform. It has been detected a total of 8,061 CNV, which 2852 are gain and 5592 are loss of a DNA segment. A great amount of sharing CNVs between Asturiana de los Valles and Morucha breeds had been observed, which suggests a proximity during their formation process. We found also 1,293 regions of CNVs, spanning 3.6% of the autosomal bovine genome and 1,263 genes were present within these regions, and were involved in biological processes such as growth and immune system